The Grouping Of Types Of Tax Revenue In Binjai City Uses The K-Means Clustering Method Algorithm - Arianti, Anita Renni; Novriyenni, Novriyenni; Ambarita, Indah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Taxes are a major source of state revenue. Without taxes, most activities of the country are difficult to implement. The use of tax money includes ranging from employee shopping to financing various development projects. Public utilities such as roads, Bridges, schools, hospitals/center facilities, police stations are financed with tax returns. Tax money is also used for financing to provide a sense of security for all levels of society. Every citizen from birth to death enjoys facilities or government services all funded with tax money.